2012
DOI: 10.1111/j.1365-2966.2012.20532.x
|View full text |Cite
|
Sign up to set email alerts
|

A QUMOND galactic N-body code - I. Poisson solver and rotation curve fitting

Abstract: Here we present a new particle‐mesh galactic N‐body code that uses the full multigrid algorithm for solving the modified Poisson equation of the quasi‐linear formulation of modified Newtonian dynamics (QUMOND). A novel approach for handling the boundary conditions using a refinement strategy is implemented and the accuracy of the code is compared with analytical solutions of Kuzmin discs. We then employ the code to compute the predicted rotation curves for a sample of five spiral galaxies from the THINGS sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…Alternatively, considerations similar to Angus et al (2012) could be made: they varied the gaseous scale-height while fitting the rotation curve of DDO 154, and found that increasing the scale-height from 0.3 kpc to 0.7 kpc reduced the χ 2 by 30%. The effect of increasing the scale-height of KK 246 would mainly be to reduce the velocity of the MOND prediction at the innermost point.…”
Section: Kk 246mentioning
confidence: 99%
“…Alternatively, considerations similar to Angus et al (2012) could be made: they varied the gaseous scale-height while fitting the rotation curve of DDO 154, and found that increasing the scale-height from 0.3 kpc to 0.7 kpc reduced the χ 2 by 30%. The effect of increasing the scale-height of KK 246 would mainly be to reduce the velocity of the MOND prediction at the innermost point.…”
Section: Kk 246mentioning
confidence: 99%
“…After the pioneering work of Brada & Milgrom (1999), only a handful of codes have been designed (Nipoti et al 2007;Llinares et al 2008;Angus et al 2012), but all with their own caveats, notably regarding the treatment of hydrodynamics. The first treatment of gas in MOND simulations was proposed by Tiret & Combes (2008a), who used sticky particles, but a full hydrodynamical treatment of gas has become possible only recently thanks to the patches of the RAMSES code developed by Lüghausen et al (2015) and Candlish et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, U ′ → 1/2 in this limit and so it is seen that the total phantom charge vanishes: q p (x)d 3 x = 0. This is clearly true also for the PL theory (10), where, again, applying a Gauss integration over the whole volume gives…”
Section: E Phantom Chargesmentioning
confidence: 81%
“…This PL version of MOND has since been put to good use for predicting and calculating MOND effects in the solar system [8] [9], for calculating MOND fields of galaxies (e.g. [10]), and structure formation in MOND [11]. Here, I essentially extend the concept to more general NL problems.…”
Section: Introductionmentioning
confidence: 99%